Degradation of selected environmental pharmaceuticals by aqueous chlorination and UV/chlorination: Kinetics, by-products, and ecotoxicity / Nur Adawiyah Mansor - Nur Adawiyah , Mansor (2018)
As emerging contaminants, some pharmaceuticals in the environment have been found to produce toxic effects to the living organism. During conventional water treatment processes, untreated pharmaceuticals are often exposed to chlorination process. Recent studies have shown that the chlorination process is not effective in removing pharmaceuticals due to its slow reaction. Hence, the focus of the study was to combine UV irradiation with chlorination (UV/chlorination) to enhance the rate of degradation of pharmaceuticals. The objectives of this study were to investigate the reaction kinetics and mechanism of the degradation of selected pharmaceuticals during chlorination and UV/chlorination. Then, the ecotoxicity of selected pharmaceuticals after chlorination and UV/chlorination was determined experimentally. The efficiency of chlorination and UV/chlorination in the removal of selected pharmaceuticals in different matrices was also evaluated. The selected pharmaceuticals for this study were 5,5-diphenylhydantoin (antiepileptic), hydrochlorothiazide (antidepressants) and tolfenamic acid (nonsteroidal anti-inflammatory drugs). For chlorination, the second-order rate constant (kapp) for the reaction between selected pharmaceuticals and free available chlorine (FAC) was determined at pH 5 to 8. The result indicated that the degradation of selected pharmaceuticals by FAC was highly pH dependence at the selected pH range. At pH 5 to 8, it was found that kapp of 5,5-diphenylhydantoin, hydrochlorothiazide and tolfenamic acid was ranged from 0.8 - 2.5 M-1 min-1, 1.6 - 70.6 M-1 min-1, and 1.0 – 41.1 M-1 min-1, respectively. For UV/chlorination, the effect of FAC dosage and pH on the degradation of selected pharmaceuticals was evaluated. UV/chlorination was found to be more effective in removing the selected pharmaceuticals as compared with conventional chlorination and UV alone. The selected pharmaceuticals degradation rate was found to increase with increasing FAC concentration. On the other hand, the degradation of selected pharmaceuticals was found to be more favorable under the acidic condition. Characterization of the transformation by-products (TBPs) formed during the chlorination of the selected pharmaceuticals were carried out using gas chromatography-mass spectrometry and liquid chromatography-triple quadrupole mass spectrometer. The TBPs for chlorination process were determined after 24 h of FAC exposure. Meanwhile, for UV/chlorination process the TBPs were identified after 6-10 min of UV/chlorination treatment. The result indicated that chlorination and UV/chlorination of pharmaceuticals could produce various TBPs via hydroxylation, chlorination, and oxidation reactions. Based on computational calculation, some of the TBPs were found to be more toxic than its parent compound. The toxicity study revealed that UV/chlorination may increased the toxicity of the pharmaceuticals solution. Hence, this study showed that detail evaluation of toxicity is required when applying UV/chlorination for the treatment of pharmaceuticals.